Generalized Ellingham diagrams for utilization in solid oxide fuel cells - Kishimoto H.; Yamaji K.; Brito M.E.; Horita T.; Yokokawa H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Generalized Ellingham diagram for the P-O-H and the Ni-P-OH systems have been constructed to investigate thermodynamically the chemical stability of nickel anode against the gaseous impurities containing phosphorous compounds. In the same way as the original Ellingham diagram, the oxygen potential is used as the vertical axis, while the temperature is adopted as horizontal axis. For the P-O-H system which contains many gaseous species, the dominant areas of gaseous species are displayed with a parameter of their partial pressure in an analogous way to the aqueous species in the Pourbaix diagram. The multicomponent Ellingham diagram for the Ni-P-O-H system was constructed in a similar manner to the multicomponent Pourbaix diagram. The obtained diagrams have been discussed to examine the reactivity of nickel anodes with phosphorus compounds in SOFCs in terms of operational variables such as temperature, oxygen potential, overpotential under the anode polarization and so on.